Modal realism, still at your convenience - Noonan, Harold; Jago, Mark (Oxford University Press, 2017)
Divers (2014) presents a set of de re modal truths which, he claims, are inconvenient for Lewisean modal realism. We argue that there is no inconvenience for Lewis.